1999
DOI: 10.1111/j.2042-3306.1999.tb05280.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeated administration of frusemide does not offer an advantage over single dosing in attenuating exercise‐induced pulmonary hypertension in Thoroughbred horses

Abstract: Summary The objective of the present study was to ascertain whether administration of a second dose of frusemide would attenuate exercise‐induced pulmonary hypertension more than a single dose. Right atrial, right ventricular and pulmonary vascular pressures were determined in 7 healthy, sound, exercise‐trained Thoroughbred horses at rest and during exercise (14.2 m/s + a 3.5% uphill grade) performed at maximal heart rate (217 ± 3 beats/min [mean ± s.e.]). Horses were studied during the following 3 treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…The theory of the alveolo-arterial membrane rupture induced by an excessive transmural pressure (West et al 1993) is generally accepted by the scientific community (Slocombe 2001). This hypothesis seems to be confirmed by recent works showing that the use of nasal strip and/or frusemide may decrease the incidence of EIPH (Goetz et al 1999;Geor et al 2001;Kindig et al 2001) while inspiratory obstruction increases the transmural capillary pressure gradient (Ducharme et al 1999).…”
Section: Discussionsupporting
confidence: 58%
“…The theory of the alveolo-arterial membrane rupture induced by an excessive transmural pressure (West et al 1993) is generally accepted by the scientific community (Slocombe 2001). This hypothesis seems to be confirmed by recent works showing that the use of nasal strip and/or frusemide may decrease the incidence of EIPH (Goetz et al 1999;Geor et al 2001;Kindig et al 2001) while inspiratory obstruction increases the transmural capillary pressure gradient (Ducharme et al 1999).…”
Section: Discussionsupporting
confidence: 58%
“…It has been observed that the blood flow in these capillaries occurs despite alveolar pressures being, at times, in excess of the capillary blood pressure (Lloyd and Wright, 1960;Thomas et al, 1961). Additional support for this suggestion derives from studies implying that capillary resistance increases when one removes the influence of the alveolar surface tension (Goetz et al, 1999;Hedenstierna et al, 1984), thus suggesting that the alveolar surface tension promotes capillary blood flow. Studies in which vascular resistance measurements were coupled with direct visualization of this microvasculature indicate that the pulmonary arterial and the venous vascular resistance increase with an increase in alveolar surface tension (by reducing surfactant), while the capillary resistance decreases with a subsequent increase in the capillary distension and recruitment (Nieman et al, 1988).…”
Section: Surface Tension Effects On Pulmonary Hemodynamicsmentioning
confidence: 89%
“…In fact, several investigators have observed open vessels in alveolar corners under zone I conditions (Goetz et al, 1999;West and Dollery, 1960) and have found that up to 15% of cardiac output goes through lungs in zone I (Koyama et al, 1989). This perfusion persists despite the fact that the vessels in the adjacent alveoli are collapsed as a result of the relatively high alveolar pressures (Anthonisen and Milic-Emili, 1966;Keilholz et al, 2001;Brudin et al, 1994;Kosuda et al, 2000).…”
Section: Zone Imentioning
confidence: 95%
See 1 more Smart Citation
“…It has been shown that the administration of furosemide 4 h before each competition reduces the risk of EIPH (Pascoe 1997;Soma et al 2000). In addition, Goetz et al (1999) showed that an additional dose of furosemide before the competition does not achieve a greater attenuation of pulmonary vascular pressure. The same authors concluded that this additional dose does not diminish the severity of the EIPH, compared to the use of a single dose.…”
Section: Treatment Of Exercise-induced Pulmonary Haemorrhagementioning
confidence: 99%